2016
DOI: 10.1093/jxb/erw347
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the Arabidopsis transcription factor bZIP29 reveals its role in leaf and root development

Abstract: HighlightbZIP29, an Arabidopsis transcription factor, is expressed in proliferative tissues and involved in the regulation of cell number in the root meristem and leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 99 publications
5
77
0
Order By: Relevance
“…Van Leene et al . reported that a group I bZIP transcription factor, bZIP29, interacts with regulatory B′ subunits of the protein phosphatase 2A (PP2A) and PP2A catalytic subunit. It is possible that subcellular localization of VIP1 and other group I bZIP members are regulated by PP2A complexes that are activated by mechanical and hypo‐osmotic stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Leene et al . reported that a group I bZIP transcription factor, bZIP29, interacts with regulatory B′ subunits of the protein phosphatase 2A (PP2A) and PP2A catalytic subunit. It is possible that subcellular localization of VIP1 and other group I bZIP members are regulated by PP2A complexes that are activated by mechanical and hypo‐osmotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical or hypo-osmotic stress transiently induces dephosphorylation of VIP1, suggesting that Arabidopsis has a VIP1 phosphatase that is activated by mechanical and hypo-osmotic stresses. Van Leene et al [31] reported that a group I bZIP transcription factor, bZIP29, interacts with regulatory B 0 subunits of the protein phosphatase 2A (PP2A) and PP2A catalytic subunit. It is possible that subcellular localization of VIP1 and other group I bZIP members are regulated by PP2A complexes that are activated by mechanical and hypo-osmotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Van Leene et al. () reported that the bZIP family member, bZIP29, was an important factor in leaf development. Taken together, these findings suggest that the candidate genes may participate in the formation of LA.…”
Section: Discussionmentioning
confidence: 99%
“…However, specific VirE2 proteins showed different, yet overlapping, specificities towards individual VIP1 homologues, potentially affecting the host range of the different bacterial species. This subset of VIP1 homologues shares somewhat redundant biological functions in uninfected cells (Tsugama et al, 2014(Tsugama et al, , 2016Van Leene et al, 2016), which suggests that this redundancy could also apply to their interactions with VirE2 during the infection process. Whereas, in nature, the host range of Agrobacterium is essentially limited to dicotyledonous plants, under laboratory conditions, many more eukaryotic species can be transformed by Agrobacterium, from monocotyledonous plants, to yeast and other fungi, to mammalian cultured cells (Lacroix et al, 2006).…”
Section: Discussionmentioning
confidence: 99%